2020
DOI: 10.1371/journal.pone.0241975
|View full text |Cite
|
Sign up to set email alerts
|

Trend and determinants of anemia change among pregnant and/or lactating women in Ethiopia: A multivariate decomposition analysis

Abstract: Background Even though anemia was highly targeted in different global strategies, many pregnant and/or lactating women and children were suffering from it and its complications. Besides this, prior trend analysis has not been conducted among pregnant and/or lactating women in Ethiopia. Therefore, this study aimed to assess the trend and determinants of anemia change among pregnant and/or lactating women in Ethiopia. Methods The study utilized two consecutive Ethiopia Demographic and Health Survey (EDHS) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The pregnant woman's region, iron taking status, number of births in the last five years, wealth index, number of antenatal care visits, health facility visits in the last 12 months, The study discovered that the pregnant woman's anemia status was greatly influenced by her geographic location. This finding is in line with research from Ethiopia [27][28][29] which found that the risk of anemia was higher in the Afar, Somali, and Dire Dawa regions. When compared to pregnant women in urban regions, pregnant women from rural areas were more likely to be in the worst category of anemia status.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pregnant woman's region, iron taking status, number of births in the last five years, wealth index, number of antenatal care visits, health facility visits in the last 12 months, The study discovered that the pregnant woman's anemia status was greatly influenced by her geographic location. This finding is in line with research from Ethiopia [27][28][29] which found that the risk of anemia was higher in the Afar, Somali, and Dire Dawa regions. When compared to pregnant women in urban regions, pregnant women from rural areas were more likely to be in the worst category of anemia status.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women with the highest economic status had the lowest risk of anemia when compared to those with the lowest economic status, according to findings from Ethiopian privies research. Studies in poor nations such as Ethiopia [27] and sub-Saharan Africa [36] back with this conclusion. This could be due to the fact that having a low salary means having less money to buy iron-rich foods or eat a well-balanced diet.…”
Section: Discussionmentioning
confidence: 86%
“…The possible justification might be women attending PNC service might have the chance to get nutritional advice. Smoking was also one of the factors responsible for anaemia among non-lactating mothers, the finding is supported by a study done in Ethiopia 24…”
Section: Discussionmentioning
confidence: 57%
“…Terminated pregnancy was also one of the determinant factors of anaemia in both lactating and non-lactating women. The finding is supported by a study done in Ethiopia 24. Women who have had their pregnancies terminated may be subjected to frequent blood loss, which in turn, results in low haemoglobin levels in the blood.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation